OPTIMIZATION SYNTHESIS CHITOSAN-XANTHAN GUM GEL FOR METAL ADSORPTION - , Purwantiningsih Sugita, Achmad Sjachriza and Dwi Wahyu Utomo ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
Shrimp shell can be used to make chitosan. Rheological properties of chitosan-xanthan gum were improved by gelation using glutaraldehyde and natural hydrocolloids xanthan gum. Rheological properties of gel measured were gel of strength, break point, rigidity, swelling, and shrinking. The chitosan-xanthan gum gel was made by mixing chitosan solution 2.50% (w/v) with variations of glutaraldehyde were 4.00, 5.00, and 6.00% (v/v), and xanthan gum 0.00, 0.75, and 1.00% (b/v), respectively. The optimum gel for metal adsorption obtained at 1.00% of glutaraldehyde and 2.40% of xanthan gum, which gave gel of strength, break point, rigidity, swelling, and shrinking properties of 725.097 g cm-2, 1.0827 cm, 6.1097 g cm-1, 10.2636 g, and 1.0008 g, respectively.